Desafios da educação em Guiné-Bissau : análise de livros didáticos de história e geografia do nono ano da educação básica, sob perspectiva da descolonização - Intanquê, Sabino Tobana (2022)
In this dissertation, we present clippings of the historical processes of education in Guinea-Bissau. We point out that, in Guinea-Bissau, before the arrival of the Portuguese colonizers, there were no modern school institutions, education occurred orally, in which teenagers and young people learned from their elders how to contribute to their communities. This education of the traditional people was colonized by the education coming from Portugal, an education based on colonization and exploitation, and when education was organized in the liberated zones during the country's independence struggle, fundamental historical milestones were established in order to understand the coloniality of knowledge and power in the current system of formal education in the country. And, in this context are the history and geography textbooks. The choice to study the content of these books was directed to the 9th grade textbooks. The study has a documental base and we used the decolonial(s) analysis of knowledge and power to problematize the Eurocentric knowledge still contained in the textbooks. By analyzing the referred textbooks, we observed contents that, for the most part, do not represent the historical and geographical reality of Guinea-Bissau, but rather, the reality of the West. Therefore, we understand that the coloniality of knowledge, being, and power represented in these textbooks represents a narrative that must and can be changed through the decolonization of these contents. And, with the inclusion of the knowledge that represents the reality of the Guinean people, it can make teenagers and young people able to (re)know their cultures, languages and realities through school education, allowing them to reflect in a deep and critical way about their past historical conditions and to project a future without the domination of these school contents. The conclusion of this work raises debates around the decolonization of the History and Geography textbooks of the country's Basic Education, and discusses the possibility of including the contents of a more critical history and geography of Guinea-Bissau in the textbooks.